The Effect of Yoga on Back Pain, Anxiety and Sleep Quality of Pregnant Women: A Systematic Literature Review - Setyowati, Eka; Widyawati, Melyana Nurul; Pramana, Cipta (GLOBAL HEALTH SCIENCE GROUP, 2025)
Pregnant women often experience various physical and psychological discomforts, such as back pain, anxiety, and sleep disorders that adversely affect maternal and fetal health. One approach that has to widely studied is yoga, which is believed to be able to reduce discomfort.Objective: To analyze and evaluate the literature regarding the effects of yoga on back pain, anxiety and sleep quality in pregnant women.Methods: This study used the Systematic Literature Review (SLR) method with the PRISMA approach. The articles analyzed were obtained from the Google Scholar, PubMed, and ResearchGate databases with the keywords